Blue Green Systems for urban heat mitigation: mechanisms, effectiveness and research directions. Issue 2 (12th December 2022) - Probst, Noëmie; Bach, Peter M.; Cook, Lauren M.; Maurer, Max; Leitão, João P.
Abstract: Reflected in the growing body of literature, urban heat mitigation is increasingly relevant as cities experience extreme heat, exacerbated by climate change and rapid urbanisation. Most studies focus on urban–rural temperature differences, known as the Urban Heat Island, which does not provide insight into urban heat dynamics. Here, we synthesise current knowledge on spatio-temporal variations of heat sources and sinks, showing that a targeted and absolute understanding of urban heat dynamics rather than an urban–rural comparison should be encouraged. We discuss mechanisms of heat sinks for microclimate control, provide a clear classification of Blue Green Systems and evaluate current knowledge of their effectiveness in urban heat mitigation. We consider planning and optimisation aspects of Blue Green Infrastructure ( greenery and water bodies/features ), interactions with hard surfaces and practices that ensure space and water availability. Blue Green Systems can positively affect urban microclimates, especially when strategically planned to achieve synergies. Effectiveness is governed by their dominant cooling mechanisms that show diurnal and seasonal variability and depend upon background climatic conditions and characteristics of surrounding urban areas. Situationally appropriate combination of various types of Blue Green Systems and their connectivity increases heat mitigation potential while providing multiple ecosystem services but requires further research. HIGHLIGHTS: Evaluation of urban heat dynamics; heat sources and sinks . Structure and systematic evaluation of different Blue Green Systems . Urban heat curtailed with strategically planned, site-specific Blue Green Systems . Cooling beyond the microscale possible with blue-green connectivity.